Implementasi Kovergensi Pencegahan dan Penurunan Stunting Melalui Banyuwangi Tanggap Stunting di Kecamatan Cluring Kabupaten Banyuwangi - Nizam Abizar Al Ghiffari; Susi Hardjati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Indonesia is still experiencing problems with malnutrition, namely undernutrition,stunting, andwasting, which are still at a high level when compared to the limit according to the World Health Organization. Referring to this problem, the Banyuwangi Regency Government carried out a convergence of stunting prevention and reduction based on Regent Regulation No. 68 of 2020. In this regulation, there is a strategic approach in the convergence of stunting prevention by carrying out a form of intervention carried out by the government through cross-sectors such as sub-district heads, police, TNI, village heads, education, Ministry of Religion, irrigation, BKKBN, and agriculture through a program echoed by the Banyuwangi Regency government, namely Banyuwangi Tanggap Stunting (BTS). The purpose of this research is to find out and analyze the implementation of stunting prevention and reduction through Banyuwangi Tanggap Stunting This research uses a qualitative approach. Data collection techniques in this study used triangulation techniques such as observation, interviews and documentation. The data analysis technique in this study uses the miles and huberman model which consists of data collection, data condensation, data presentation and data conclusions. This research produces interesting findings including: 1) in the aspect of policy standards and objectives, it has been said that it is quite good and has clear objectives, for example, the standard of the policy set in the Regent Regulation where the target prevalence of stunting reduction is at least 1% every year 2) in the aspect of resources, it is good because from a financial point of view, Cluring Sub-district has a large budget allocation for Resti pregnant women and stunting baduta 3) in the aspect of organizational characteristics of implementers Each policy implementer has run well. OPD carries out their respective duties and roles in accordance with what is stated in the Cluring Sub-district Decree 4) on the communication aspect, it has been running well because OPD coordinates both formally and informally through FGD meetings at Mini Loka Karya, besides always communicating through WA groups to convey the results of discussions to the community. 5) in the attitude aspect, the OPD implementers accept the form of policy with a positive response 6) and finally in the socio-economic and political aspects, it has gone well because they feel helped by the policy.